Measures of human development: a narrative - Vasthare, Ramprasad; Dhaundiyal, Shriya; Puri, Sunaina (International Journal Of Community Medicine And Public Health, 2019)
Human development is a direct function of human capability, understood through the different facets of the human development index. The impact of gender inequality, women empowerment, environmental and socioeconomic sustainability has also been described in this review. It brings forth and reinforces that national development is an assessment of not only per capita income but by other influential factors which affect development comprehensively, such as educational achievements and health. A thorough primary screening was done for articles on human development index using the data bases of PubMed, Scopus and Google Scholar using the key words human development, United Nations, measures, indicators and index, followed by a secondary screening, with due concern to avoid overlap of information. The articles were categorized based on the subject of Human Development with due prioritization. Human development index has evolved periodically taking into consideration the developments, limitations and criticisms. It has become an important indicator of human progress and serves as a guide to state, societal, community and individual developments. India currently holds a rank of 130 denoting medium human development.